If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y = 2y + 35 Reorder the terms: 9y = 35 + 2y Solving 9y = 35 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 9y + -2y = 35 + 2y + -2y Combine like terms: 9y + -2y = 7y 7y = 35 + 2y + -2y Combine like terms: 2y + -2y = 0 7y = 35 + 0 7y = 35 Divide each side by '7'. y = 5 Simplifying y = 5
| v^2-2=65 | | 2y+1=23 | | 12k-32=24 | | -n+1-7n=9-7n | | -3+6x=x+7 | | z+3.6=2.5 | | -0.24p+1.602=1.29 | | 1X+4Y=58 | | -5x-10=-3+2x | | 7(n-4)-(6-3n)=9n | | 0,001*0,001x=1/8 | | 2+3x=-5x-6 | | 2x-5=-2+x | | H=0.001x^2-X+27 | | 12h=72 | | (x+4)+(x+2)+(x+5)=2(x+1)+2(x+3) | | 90m^2+21mn-6n^2=0 | | T-75H=735 | | 9x+7-7x=4+x+5 | | -2=6+2x | | -20=b-5 | | 8-n=6+4n | | -9+7m=1+5m | | (m+2)(m-2)=0 | | 3(5-q)+6=9 | | 5(x+2)-(2x-7)= | | 10g=1100 | | x+4+x+2+x+5=2(x+1)+2(x+3) | | 10=1100 | | 3x-6=-14-7+6x+6 | | m^2-6m-33=-6 | | 5x-2=2x-35 |